Circular RNA circ‐TNRC6B inhibits the proliferation and invasion of esophageal squamous cell carcinoma cells by regulating the miR‐452‐5p/DAG1 axis - Ruiyu Xu; Pingan Ding; Xiaoru Zhao; Ziyi Li; Fei Liu; Lina Gu; Yang Zheng; Meixiang Sang; Lingjiao Meng (Molecular Oncology, 2023)
Previous studies have uncovered the key role of circular RNAs (circRNAs) in various diseases, including cancer. However, the growth‐inhibitory effects of circRNAs on esophageal squamous cell carcinoma (ESCC) have not been completely elucidated. This study characterized a newly identified circRNA derived from exons 9–13 of TNRC6B (named circ‐TNRC6B). The expression of circ‐TNRC6B in ESCC tissues was markedly downregulated when compared to that in non‐tumor tissues. In 53 ESCC cases, circ‐TNRC6B expression was negatively correlated with the T stage. Multivariate Cox regression analysis showed that circ‐TNRC6B upregulation was an independent protective factor for ESCC patients' prognosis. Overexpression and knockdown functional experiments demonstrated that circ‐TNRC6B inhibited ESCC cell proliferation, migration, and invasion. RNA immunoprecipitation and dual‐luciferase reporter assays demonstrated that circ‐TNRC6B sponges oncogenic miR‐452‐5p to upregulate the expression and activity of DAG1. Treatment with miR‐452‐5p inhibitor partially reversed the circ‐TNRC6B‐induced changes in the biological behavior of ESCC cells. These findings demonstrated that circ‐TNRC6B exerts a tumor‐suppressing effect in ESCC through the miR‐452‐5p/DAG1 axis. Thus, circ‐TNRC6B is a potential prognostic biomarker for the clinical management of ESCC.